Adaptation and Mitigation Strategies of Climate Change From Agricultural Sector In the Tabalong District (South Borneo) - Rian Yaitsar Chaniago; Rachmat Boedisantoso; Arie Dipareza Syafei (JURNAL SOSIAL HUMANIORA (JSH), 2022)
Agriculture and climate change have a complex causal relationship. The agricultural sector produces large amounts of Green House Gases (GHG) such as CH4, CO2, and N2O which affect the climate. One of the consequences of climate change is an increase in rainfall. This has caused 2,971.51 ha of submerged and damaged rice fields in the Tabalong District. This study aims to determine the climate change adaptation and mitigation strategies of the agricultural sector in the Tabalong District. Emission measurements and mapping of the distribution of GHG emissions are shown to support strategy determination. The GHG inventory is calculated using the Indonesian Ministry of Environment and Forestry method, mapping the distribution of emissions using the geographic information system method, and determining the best adaptation and mitigation strategies using the Analytic Hierarchy Process (AHP) with Expert Choice Software. The results showed that GHG emissions from the agricultural sector of the Tabalong District until 2030 amounted to 191,384 tCO2e / year.  There are five Sub-districts identified as the largest GHG-producing districts from the mapping of the distribution of GHG. The results of the AHP synthesis show that there are three strategies for climate change adaptation and four strategies for climate change mitigation